Connectedness to Nature: Its Impact on Sustainable Behaviors and Happiness in Children - Barrera-Hernández, Laura Fernanda; Sotelo-Castillo, Mirsha Alicia; Echeverría-Castro, Sonia Beatriz; Tapia-Fonllem, César Octavio (Frontiers in Psychology, 2020)
Given the environmental problems humanity is currently facing, and considering that the future of the planet lies in the hands of children and their actions, research about the determinants of sustainable behaviors in children become more relevant; nonetheless, studies on this topic focusing on children are scarce. Previous research on adults suggest, in an isolated manner, the relationship between connectedness to nature, the development of behaviors in favor of the environment and positive results derived from them, such as happiness and well-being. In the present research, connectedness to nature was considered as a determinant of sustainable behaviors, and happiness as a positive consequence of the latter. This research aimed to demonstrate the relationship between these variables in children. Two hundred and ninety six children with an average age of 10.42 years old participated in the study, who responded to a research instrument that measured connectedness to nature, sustainable behaviors (pro-ecological behavior, frugality, altruism, and equity) and happiness. To analyze the relationships between these variables, a model of structural equations was specified and tested. The results revealed a significant relationship between connectedness to nature and sustainable behaviors, which in turn impact on happiness. This suggests that children who perceive themselves more connected to nature tend to perform more sustainable behaviors; also, the more pro-ecological, frugal, altruistic, and equitable the children are, the greater their perceived happiness will be. The implications for studying and promoting sustainable behaviors are discussed within the framework of positive psychology.